Optimization of Fishery Product Quality Assessment in Dumai through Multivariate Analysis Based on Organoleptic Testing - Pratiwi, Merina; Syarief, Amiroel Oemara (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
The quality of fishery products is a critical factor influencing competitiveness and market acceptance, particularly for the fishery industry in Dumai City. However, assessing fishery product quality remains challenging, primarily due to the subjective nature of organoleptic testing, which is often influenced by variability in panelists' evaluations. This subjectivity can lead to inconsistencies in assessment results and reduce the reliability of quality evaluations. This study aims to optimize the quality assessment of fishery products by applying discriminant analysis, a multivariate analysis method based on organoleptic testing. We conducted the organoleptic test by evaluating six key sensory parameters: appearance, odor, taste, texture, mold presence, and slime. This approach seeks to minimize subjectivity in assessments and enhance the objectivity of results. The fishery product samples tested included a variety of local products, such as smoked catfish, shrimp paste, smoked patin fish, shrimp crackers, salted tonguefish, fish crackers, swordfish nuggets, patin nuggets, swordfish meatballs, catfish meatballs, and patin meatballs. Evaluations were conducted by trained panelists with the support of digital tools to improve the consistency and accuracy of results. The discriminant analysis results indicated that the model could classify product quality with an accuracy of up to 83.3%. Taste was identified as the most significant sensory factor in distinguishing high-quality products from lower-quality ones.